Graduate Students Experiences of Learning Community in Relation to Self-Determined Motivation - Karaçul, Fikriye Eda (Advances in Social Sciences Research Journal, 2018)
This study attempted to explore the effect of inter- and intra-personal perceptions and practices of graduate students on their academic motivation from a Self Determination Theory perspective. Students in a large research university were surveyed to determine whether there is any association between their sense of learning community, the need for relatedness, and their reasons to be in graduate school. This study provides evidence to support the importance of the fulfillment of the need to belong in learning community. Differences between international and non-international students represented when they were engaged in their coursework as analyzed by using Ryan and Deci’s (2000) Self Determination and Tajfel and Turner’s (1979) Social Identity Theory.